2007
DOI: 10.1124/jpet.107.124958
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 Receptor Antagonists: Correlation between in Vitro Receptor Interaction and in Vivo Efficacy

Abstract: We compared the neurokinin 1 receptor (NK 1 R) antagonists aprepitant, CP-99994 [(2S,3S)-3-(2-methoxybenzylamino)-2-phenylpiperidine], and ZD6021 [3-cyano-N-((2S)-2-(3,4-dichlorophenyl)-4-[4-[2-(methyl-(S)-sulfinyl)phenyl]piperidino]butyl)-N-methyl]napthamide]] with respect to receptor interactions and duration of efficacy in vivo. In Ca 2ϩ mobilization assays (fluorometric imaging plate reader), antagonists were applied to human U373MG cells simultaneously with or 2.5 min before substance P (SP). In reversibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 47 publications
6
48
0
1
Order By: Relevance
“…This effect was partially reversible by adding NK1R agonists such as SP. This latter finding identified the targeting effect of the used NK1R inhibitor to be specific (SP's is known to have a stronger binding affinity than most NK1R inhibitors, including aprepitant) (19,27). These data are in accordance with our own findings recently published for hepatoblastoma and osteosarcoma (22,23).…”
Section: Therapeutic Innovations In Neuroblastomasupporting
confidence: 82%
See 1 more Smart Citation
“…This effect was partially reversible by adding NK1R agonists such as SP. This latter finding identified the targeting effect of the used NK1R inhibitor to be specific (SP's is known to have a stronger binding affinity than most NK1R inhibitors, including aprepitant) (19,27). These data are in accordance with our own findings recently published for hepatoblastoma and osteosarcoma (22,23).…”
Section: Therapeutic Innovations In Neuroblastomasupporting
confidence: 82%
“…This mechanism seems to rely in part on β-arrestin/clathrin proteins and seems to be crucial for this receptor system's innate inhibitory feedback loop. Importantly, a splice variant of the NK1R was recently described that seems to have important implications in carcinogenesis by breaking up the receptor's innate feedback loop (19,20).…”
Section: Therapeutic Innovations In Neuroblastomamentioning
confidence: 99%
“…The gene and protein levels of MMP-12, MMP-9, TIMP-1, and NK1R in AMs were detected in the first and second groups, respectively. The same protocols were repeated in the third and fourth groups, with the exception that CP-99,994 was replaced by aprepitant (10 Ϫ8 M; Merck), another NK1R antagonist (18,33) used in clinic (21). The doses of SP, CP-99,994, and aprepitant were chosen because several investigators have shown that they could sufficiently activate or block NK1R in the cells (28,33,56).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, to demonstrate an additional value in vivo with an enhanced residence time measured in vitro, carefully designed studies which monitor efficacy (blood pressure lowering) together with compound exposure levels at the assumed site of action (kidney and/or plasma) are required. Nevertheless, it has been demonstrated that the tachykinin NK 1 receptor antagonist aprepitant, with demonstrated prolonged residence time at the NK 1 receptor in vitro compared to other equipotent antagonists, produced longer efficacy duration in vivo (Lindström et al 2007). The prolonged in vivo efficacy of aprepitant was not explained by differences in pharmacokinetics between compounds, but was more likely due to slowly dissociating receptor complexes.…”
Section: Discussionmentioning
confidence: 98%